Dermoscopic Image Digital Post-Processing Perception and Use Among Members of theInternational Dermoscopy Society: Results of a Web-based Survey - Marian Voloshynovych; Paweł Pietkiewicz; Cristián Navarette-Dechent; Aimilios Lallas; John Paoli; Harald Kittler; Ashfaq A. Marghoob; Mohamad Goldust; Jacek C. Szepietowski; Iris Zalaudek; Thomas M. Beachkofsky; Caterina Longo; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Speculatively, digital image post-processing (DIPP) enhances diagnostic accuracy in dermoscopy.